RAËLISM: AN UNCONVENTIONAL RELIGIOUS PATHWAY TO TRANSHUMANISM. - Yeşilyurt, Büşra; Yeşilyurt, Muhammet (Ilahiyat Studies)
Raëlism is a controversial new religious movement that originated in France in the 1970s and has since spread around the world. The movement's core tenets are rooted in science, technology, and freedom and can be summarized as a blend of science and spirituality, millenarianism, revelation, story, pseudoscience, and reinterpretation. Raëlians believe in the extraterrestrial origin of humanity and promote the pursuit of higher consciousness, inner peace, individual empowerment, and peace-building. To this end, the movement offers a series of seminars that aim to provide a transformative experience for participants and leads various social initiatives and projects at a global level. Although Raëlism has gained popularity among some individuals, it has also been the subject of substantial criticism and controversy, particularly because of its unconventional views on sexuality and its alleged support for human cloning and genetic engineering. Nonetheless, the movement continues to be a subject of interest and scrutiny for scholars, journalists, and the curious. This article provides an overview of the history, ideology, and practices of the Raëlian Movement and its relationship with transhumanism.